João Apolinário e Sábato Magaldi: estética e história na crítica teatral brasileira - Pinto, Tânia Maria de Oliveira Teixeira (2023)
This thesis focuses on the comparative analysis of theatrical criticism by João Apolinário and Sábato Magaldi, two important critics who worked during a significant period in the history of Brazilian theater, marked by the military dictatorship and artistic effervescence between 1966 and 1971. general objective is to study the critical approaches of Apolinário and Magaldi, understanding how their analyzes influenced the theatrical production of the time, as well as to investigate the historical and social context in which these criticisms were produced. The methodology adopted involved, in addition to the analysis of selected critics, bibliographical research to contextualize the history of theater criticism in Brazil and the function of the critic as a mediator between the work and the public. The research results highlight the similarities and differences in Apolinário and Magaldi's approaches, revealing how their analyzes reflected the particularities of Brazilian theater at the time. Both authors' criticisms are also analyzed in light of the political and social context of Brazil under the military dictatorship, showing how theater became a means of artistic and political expression. The thesis contributes to filling a gap in the history of Brazilian theater criticism by valuing and analyzing the contributions of João Apolinário and Sábato Magaldi, offering a deeper understanding of the role of criticism in the construction and reflection of the national theater during a challenging period. In addition, the comparative analysis between the two critics provides insights into the diversity of critical approaches and their influence on the understanding of the theatrical scene